Transformation Poem Nyanyian Angsa by W. S. Rendra to Novel Maria Zaitun by Joko Santoso: Intertextual Study - Nesya Yanmas Yara; Sarwaji Suwandi; Sumarwati Sumarwati (Budapest International Research and Critics University, 2019)
The transformation of literary work today began to flourish in the field of literary studies, especially from novel to film form. The process of transformation on the form of poetry to other forms is still rare, but in this study researchers managed to find transformation from the poem Nyanyian Angsa by W. S. Rendra to novel Maria Zaitun by Joko Santoso. This research aims to describe the form of additions, substitutions, and differences in the poetry Nyanyian Angsa by W. S. Rendra and novel Maria Zaitun by Joko Santoso. The theory used in this study is transformation with qualitative descriptive research methods. The source of this research data is the poem text Nyanyian Angsa by W. S. Rendra and novel Maria Zaitun by Joko Santoso. Data collection techniques using reading techniques and note taking techniques, as well as interactive data analysis from Miles & Huberman (1992). The results of this study showed that additions, substitutions, and differences from poetry to novels found similarities and differences. The difference is because the building elements of the two literary works are different, but overall the literary works have similarities.